Committee 'B' on Draft Third Five Year Plan (Industry, Power and Transport) Synopsis of Proceedings (10th, 11th and 12th November, 1960) - Planning Commission (Planning Commission, 1960)
The Chairman, at the outset, welcomed the Members of the Committee and the Deputy Chairman and the Members of the Planning Commission who were present at the sitting. He further dwelt upon the handicaps and difficulties under which the Committee had to function. He shared the feeling of Members that they might have had more time than the three days fixed for discussion but expressed the view that the advantage of concluding their discussion earlier would be that on account of certain factors which were inherent in the situation, they would have greater chances of influencing the decision of the Planning Commission. The Chairman further referred to the various topics for discussion by the Committee and suggested taking them up according to the order in which they were listed in the List of Topics, i.e. taking up Industries and Minerals first of all. With regard to the speeches by the Members he suggested that judging from the experience of the Committee last time when the Second Plan was being discussed, the best contribution which the Members of Parliament at the Committee stage could make would be to have some concrete points on each sub-topic so that they could give brief arguments in support of those and the chances of that going down were much greater than if the discussion was discursive or if very lengthy arguments were given. He said that this was also in the interest of the Members because the longer the speech by one Member the time avail- able for the others was obviously, to that extent, reduced. He, therefore suggested that in mutual interest it was desirable to have some brief discussion on concrete points and give the main arguments as concisely as was possible.
Lok Sabha Secretariat New Delhi
Lok Sabha Secretariat New Delhi